How impact fees and local planning regulation can influence deployment of telecoms infrastructure - Paul Gorecki; Hugh Hennessy; Sean Lyons (International Telecommunications Society (ITS), 2011)
This paper examines how local government planning regulations and charges affect the deployment of telecommunications infrastructure. We explore the economic rationale for local government regulation of such infrastructure, which we suggest should be based on managing negative externalities. Using data from Ireland, we find that the observed geographical pattern of impact fees is inconsistent with the economic rationale for them. A simple econometric model of the number of telecoms masts in each country also suggests that the level of impact fees is negatively associated with mast deployment. This paper also examines other regulatory factors that affect the provision of new infrastructure. We find wide regional variation in these regulations but are unableto quantify their impact on infrastructure provision. Such regulatory complexity places extra compliance burdens on private operators, which may in turn distort the level and regional pattern of network investment. We suggest further regional harmonisation of development policy towards telecoms infrastructure to avoid exacerbating regional disparities in rollout of services.
Keywords: H71; L96; R38; R52; 330; Land use regulation; telecommunications infrastructure investment; impact fees